Manual and semi-automated approaches to MIBG myocardial scintigraphy in patients with Parkinson’s disease - Boccalini, Cecilia; Carli, Giulia; Vanoli, Emilia Giovanna; Cocco, Antoniangela; Albanese, Alberto; Garibotto, Valentina; Perani, Daniela (Frontiers in Medicine, 2022)
Objective This study investigates the effects of manual and semi-automatic methods for assessing MIBG semi-quantitative indices in a clinical setting. Materials and methods We included 123I-MIBG scans obtained in 35 patients with idiopathic Parkinson’s Disease. Early and late heart-to-mediastinum (H/M) ratios were calculated from 123I-MIBG images using regions of interest (ROIs) placed over the heart and the mediastinum. The ROIs were derived using two approaches: (i) manually drawn and (ii) semi-automatic fixed-size ROIs using anatomical landmarks. Expert, moderate-expert, and not expert raters applied the ROIs procedures and interpreted the 123I-MIBG images. We evaluated the inter and intra-rater agreements in assessing 123I-MIBG H/M ratios. Results A moderate agreement in the raters’ classification of pathological and non-pathological scores emerged regarding early and late H/M ratio values (κ = 0.45 and 0.69 respectively), applying the manual method, while the early and late H/M ratios obtained with the semi-automatic method reached a good agreement among observers (κ = 0.78). Cohen-Kappa values revealed that the semi-automatic method improved the agreement between expert and inexpert raters: the agreement improved from a minimum of 0.29 (fair, for early H/M) and 0.69 (substantial, in late H/M) with the manual method, to 0.90 (perfect, in early H/M) and 0.87 (perfect, in late H/M) with the semi-automatic method. Conclusion The use of the semi-automatic method improves the agreement among raters in classifying’ H/M ratios as pathological or non-pathological, namely for inexpert readers. These results have important implications for semi-quantitative assessment of 123I-MIBG images in clinical routine.